Genome Sequencing and Comparative Genomics of Indian Isolates of Brucella melitensis - Karthik, Kumaragurubaran; Anbazhagan, Subbaiyan; Thomas, Prasad; Ananda Chitra, Murugesan; Senthilkumar, Tuticorin Maragatham Alagesan; Sridhar, Ramaswamy; Dhinakar Raj, Gopal (Frontiers in Microbiology, 2021)
Brucella (B.) melitensis causes small ruminant brucellosis and a zoonotic pathogen prevalent worldwide. Whole genome phylogeny of all available B. melitensis genome (n= 355) revealed that all Indian isolates (n=16) clustered in East Mediterranean lineage except ADMAS-GI strain. Pangenome analysis indicated the presence of limited accessory genomes with few clades showing specific gene presence/absence pattern. A total of 43 virulence genes were predicted in all the Indian strains of B. melitensis except 2007BM-1 (ricA and wbkA are absent). MLST analysis indicated all except one Indian strain (ADMAS-GI) falling into sequence type (ST 8). In comparison to MLST, core genome phylogeny indicated two major clusters (> 70 % bootstrap support values) among Indian strains. Clusters with < 70 % bootstrap support values represents strains with diverse evolutionary origins present amongst animal and human hosts. Genetic relatedness among animal (sheep and goats) and human strains with 100 % bootstrap values showing its zoonotic transfer potentiality. SNPs based analysis indicated similar clustering to that of core genome phylogeny. Among the Indian strains, highest number of unique SNPs (112 SNPs) were shared by a node that involved three strains from Tamil Nadu. The node SNPs involved several peptidase genes like U32, M16 inactive domain protein, clp protease family protein and M23 family protein and mostly represented non-synonymous (NS) substitutions. Vaccination has been followed in a several parts of the world to prevent small ruminant brucellosis but not in India. Comparison of Indian strains with vaccine strains showed that M5 is genetically closer to most of the Indian strains than Rev.1 strain. The presence of most of the virulence genes among all Indian strains and conserved core genome compositions suggest the use of any circulating strain/genotypes for the development of vaccine candidate for small ruminant brucellosis in India.